Implementation of character education through children's story e-books for elementary school students - Ery Maritim; Ngatmini; Achmad Buchori (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2025)
This study aims to analyze the implementation of character education through children's story e-books for students at SD Negeri 02 Tanjungsari, Pemalang Regency. The research subfocus includes planning, implementing, and evaluating the character education program. A qualitative approach with a descriptive research design was used. Data were collected through observations, interviews, and documentation. The research results indicate that in the planning stage, the school has formulated a vision and mission incorporating character education values, developed an integrative curriculum, and allocated a budget and facilities for children's story e-books as digital literacy media. Character education is integrated into learning and extracurricular activities in the implementation stage. In the classroom, teachers use various teaching methods that reflect character development, while outside the classroom, character education is carried out through extracurricular activities, habituation programs, the School Literacy Movement (GLS), The School Literacy Movement (GLS) plays a significant role in this process by encouraging reading and other literacy practices that promote critical thinking, ethical decision-making, and cultural awareness. The Strengthening Pancasila Student Profile (P5) project and active collaboration between the school and parents. The conclusion of this study shows that implementing character education through children's story e-books can enhance character development and lead to more positive behavioral changes. The recommendations include more diverse e-book content development and intensive training for teachers to utilize digital media effectively. A suggestion for future research is the development of technology-based evaluation methods to objectively measure students' character changes.